KLASIFIKASI STATUS KERJA PADA ANGKATAN KERJA KOTA SEMARANG TAHUN 2014 MENGGUNAKAN METODE CHAID DAN CART - Novie Eriska Aritonang; Agus Rusgiyono; Rita Rahmawati (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
The growth of labor will increase along with increasing population. Increasing the number of this labor of course going to have an impact on his status, whether employ or unemployed. The method can be used to classify the status of the labor is CHAID (Chi-squared Automatic Interaction Detection) and CART (Classification and Regression Trees). Both of these methods aim to identify factors that influence employment status. These methods will be applied for Semarang labor data in 2014. Based on CHAID method, the factors that affect the status of the labor is gender, age and status of the completeness of a life partner with accuracy classification results amounted to 72.63%. Factors that affect the status of the labor force with the CART method is gender, age, educational status, and the status of the completeness of a life partner with the accuracy of the classification is 72.79%. Based on proportion test, these methods are same of doing classification employment status.Keywords: Labor, Classification, CHAID, CART, Accuracy of classification